2020
DOI: 10.1155/2020/4732490
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Ground and Air Temperature Fields of a Cold‐Region Road Tunnel in NW China

Abstract: To fully understand the temperature distribution of cold regions and the variation law of temperature fields in cold-region tunnels, this paper presents a case-history study on a tunnel located on the eastern Qinghai-Tibet Plateau, China. The conclusion is as follows: the temperature outside the tunnel and the ambient temperature are affected by wind speed and light. The law of the temperature field in the tunnel is greatly affected by wind speed and wind direction. According to the field test, the wind speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Compared with the results measured in the field, we have to admit that numerical simulations cannot reflect the actual situation. erefore, currently we mainly rely on monitoring to identify the structure states to ensure the safety of underground construction [44][45][46]. However, numerical simulations perform well in regularity analysis [47][48][49][50][51][52][53][54][55].…”
Section: Distribution Of Surface Settlementmentioning
confidence: 99%
“…Compared with the results measured in the field, we have to admit that numerical simulations cannot reflect the actual situation. erefore, currently we mainly rely on monitoring to identify the structure states to ensure the safety of underground construction [44][45][46]. However, numerical simulations perform well in regularity analysis [47][48][49][50][51][52][53][54][55].…”
Section: Distribution Of Surface Settlementmentioning
confidence: 99%
“…It could be concluded that excavation programs I and II had little effect on the rock mass settlement of the newly built tunnel and sedimentation characteristics were similar. Based on the above numerical analyses, it could be concluded that, according to the Code for Monitoring Measurement of Urban Rail Transit Engineering (GB50911-2013) [4,7], the maximum allowable value of surface settlement reached 20 mm and surface settlement rate reached 4 mm/day as a control node for surrounding rock stability which could effectively guarantee the safe construction of surrounding rock and effectively control construction efficiency. It was also found that the corresponding maximum settlement values of rock mass obtained for excavation programs I and II were 12.60% and 12.67% of the maximum allowable settlement value, respectively, indicating that the rock masses of the newly built left and right lines were under relatively stable and safe construction conditions.…”
Section: Deformation Characteristics Of Newly Built Tunnelmentioning
confidence: 99%
“…In particular, in urban underground space engineering practices, new tunnels would inevitably underpass the existing buildings and important traffic lines. erefore, the excavation of new tunnels disturbs the strata surrounding tunnel body and even affects the safe use of adjacent existing buildings [7][8][9][10]. When a new underground rock mass project is executed near a high-speed railway tunnel, which poses unprecedented challenges to the safe construction of underpass [11][12][13][14][15][16], strict requirements are imposed on the settlement and deformation of surrounding rocks due to the existing high-speed railway line [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of salt rock at different loading rates shows some variation. Therefore, it is of great significance to study the mechanical properties of salt rock at different loading rates to ensure the safety and stability of underground gas storage (Chen et al., 2020; Wang et al., 2020a; Wu et al., 2020b).…”
Section: Introductionmentioning
confidence: 99%